Seismic behavior of tall building structures by friction damper - Shoushtari, Abdollah Vaez (2010)
Large-magnitude long-distance earthquakes generated from Sumatra have significant potential engineering implications in Singapore and Malaysia Peninsula due to accentuation by resonance in buildings. Historical seismicity data of the region covering the past 100 years shows numerous occasions when low-intensity seismic waves reached Peninsular and hence no seismic provisions have been incorporated into building regulations to date. If part of input energy due to earthquake could be dissipated through special devices which can be easily be replaced, as necessary, after an earthquake, the structural damage could be reduced. These devices can be classified into three categories: viscous and viscoelastic dampers, metallic dampers, and friction dampers. The purpose of this study is to evaluate the seismic behavior of tall building structures by friction damper. The finite element modeling technique (SAP2000 Software) is used in this study to learn the behavior of structure equipped by friction dampers. Three different methods of analyzing (Free vibration, Response spectrum, and Time History analysis) have been done to achieve this purpose. In general, this study indicates that the response of structure such as story drifts, axial load of columns and beams, shear load and bending moment of beams, and base shear can be dramatically reduced by using friction damper devices. In addition, this study indicates that the seismic risks due to large-magnitude, long-distance earthquakes generated from Sumatra should be considered for the tall buildings in Malaysia and the application of the seismic retrofitting to existing buildings is much needed to safeguard structure from external peak ground acceleration intensity.